The different approach for supercapacitor modelling in the perspective of self-discharge study - Muhammad Abdul Jabbar Bin Abu Bakar; Muhammad Izuan Fahmi; Shamshul Bahar Yaakob; Liew Hui Fang; Muhammad Zaid Aihsan (Institute of Advanced Engineering and Science, 2022)
Supercapacitor is a relatively new type of electric component used to store energy compared to a battery. Supercapacitor charge and discharge cycle are faster compared to the battery along with higher power density which increase its application in recent years. However, supercapacitors have quite high self-discharge compared to batteries. This makes energy stored in supercapacitor decrease faster over time when not in use. Various study has been done towards the self-discharge behavior of SC which is both experimentally and in simulation. The simulation is done by various methods and models which have been proposed by previous researchers. Most of the methods that have been used were based on the Equivalent Circuit Model as it is the easiest method available. However, there is still another method proposed such as the Fractional-order model. This paper will review some of the methods and models used to study self-discharge behavior.